Intégration des principes de développement durable au collégial : Le cas du programme de Techniques de tourisme - Marie-Janou Lusignan (VertigO)
Year after year, an increasing number of tourists are travelling across the world, and this increase in tourist travels is not without impacts on the natural, social and cultural environment or on the local economy and the development of communities. To understand the issues, their impacts and the manner in which they can be lessened, the Tourism Techniques program at the Cégep de Granby-Haute-Yamaska is focusing its training program on sustainable and responsible tourism. It all started with some of the teachers being interested with sustainable development. Awareness progressively spread through the department. It is now recognized that education in sustainable development is a fundamental component of the Tourism Techniques program. For the last ten years, the program has been engaged in a progressive, step-by-step implementation of a number of specific actions aimed at integrating sustainable development principles to its training. The objective is first to educate responsible citizens and professionals to ensure that the next generation is better equipped to play its part as actors of change in its environment. A good understanding of the issues is required to attain this goal. Secondly, the objective is to meet the needs and expectations of the employers in this matter. The present article aims at providing an overall picture of the various initiatives and endeavors developed by the Tourism Techniques program to integrate sustainable development in its curriculum.